A study of The impact of Antibiotic Pollution and The types of Environmental Pollution It causes - Sara Abdalkareem Moshref (International Journal of Antibiotics, 2026)
Antibiotics are essential biological drugs for human health and are the cornerstone of treating infections caused by various bacteria and viruses. However, they also pose a significant risk if misused, as each antibiotic is designed for a specific type of bacteria. Sometimes, due to the evolution of bacteria, many antibiotics have become ineffective and resistant to contamination and infection. Therefore, they can have the opposite effect, polluting the environment instead of eliminating bacteria, thus increasing the risk of antibiotic-associated contamination. Environmental scientists and chemists have warned that chemical pollution poses a threat to human well-being and nature, a threat comparable to global warming and climate change, yet it receives less public attention and awareness, and serious measures to contain it are not being taken. Chemical, biological, and viral-bacterial pollution has become widespread in the environment. This research examines methods for eliminating chemical and biological pollutants from the environment, some of which involve using chemical blocking agents known in analytical chemistry, as well as chemical separation and extraction methods for pollutants. Some environmental studies indicate that the industrial economy has created more than 100 million new chemicals, meaning they do not exist in nature of these, between 40,000 and 350,000 are in widespread commercial use and production. Chemical pollution is linked to biological pollution, as aquatic organisms—plants, animals, and microorganisms—are affected by the forms of chemical pollution present in the aquatic environment. Chemical pollutants, in all their forms and types, affect the growth, reproduction, and spread of aquatic organisms within their habitats.
Keywords: Bacteria; Environment; Pollution; antibiotics; economy